1993
DOI: 10.1016/0735-1097(93)90318-u
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled comparison of antitachycardia pacing algorithms for termination of ventricular tachycardia

Abstract: In the patients studied, adaptive antitachycardia pacing was safe and effective and, when successful, occurred within three attempts of an 8-beat adaptive burst algorithm. Changes in burst pattern did not affect pacing safety or efficacy. Antitachycardia pacing success was dependent on induced ventricular tachycardia cycle length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 11 publications
1
22
0
4
Order By: Relevance
“…However, in the PainFREE trials the efficacy of ATP was evaluated in spontaneous arrhythmias in comparison with induced arrhythmias in the current study. It has been previously shown that the efficacy of ATP is less, and the risk of acceleration is higher for induced arrhythmias, compared to spontaneous arrhythmias 13–18 . The authors expect the success rate of ATP would be higher in spontaneous VT compared to the induced VT seen in this study.…”
Section: Discussionsupporting
confidence: 46%
“…However, in the PainFREE trials the efficacy of ATP was evaluated in spontaneous arrhythmias in comparison with induced arrhythmias in the current study. It has been previously shown that the efficacy of ATP is less, and the risk of acceleration is higher for induced arrhythmias, compared to spontaneous arrhythmias 13–18 . The authors expect the success rate of ATP would be higher in spontaneous VT compared to the induced VT seen in this study.…”
Section: Discussionsupporting
confidence: 46%
“…Although ATP therapy has been proven safe and effective in terminating both slow and fast VT, most of the studies to date include patients whose devices were implanted for secondary prevention purposes 6, 7 , 12–18 . Although the Pacing Fast Ventricular Tachycardia Reduces Shock Therapies (PainFREE Rx II) Trial did include a primary prevention population, the study was done before the adoption of MADIT II and SCD‐HeFT indications, and over half of the patients had spontaneous VT or VF 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the effectiveness of ATP for spontaneous VT events is in the 85–96% range 6–8 . ATP success is contingent on the pacing stimulus penetrating an “excitable gap” in the circuit, and colliding both antidromically with the “head” of the VT wavefront and orthodromically with the VT “tail” at a point of absolute refractoriness, thus extinguishing the tachycardia 9 .…”
Section: Discussionmentioning
confidence: 99%